PELAKSANAAN FUNGSI PENGAWAS KETENAGAKERJAAN DALAM MENGAWASI PENERAPAN UPAH MINIMUM PROVINSI DI DAERAH KHUSUS IBUKOTA JAKARTA - Darwati; Lucky Ferdiles (Constitutum: Jurnal Ilmiah Hukum, 2025)
The relationship between workers and employers is regulated in an agreement, either in written or oral form. Law Number 13 of 2003 concerning Manpower regulates the rights and obligations of employers and workers. Article 90 states that employers are prohibited from paying workers wages below the minimum wage. However, PT. Guna Bangun Jaya paid workers wages below the minimum wage, and the Labor Inspector determined that the employer is obliged to pay the workers' wage shortfall. Against this determination, the employer filed a lawsuit with the State Administrative Court and the lawsuit was rejected. Regarding the employment relationship, the Industrial Relations Court stated that there was no employment relationship. Subsequently, the Head of the Manpower Sub-Department revoked the Manpower Inspector's determination. This study discusses the implementation of the Manpower Inspector's function in supervising the implementation of applicable regulations and the cancellation of the determination made by the Head of the Manpower Sub-Department. This study uses normative and empirical juridical research methods. The results of the study explain that the implementation of the Manpower Inspector's function is to provide guidance to companies that commit violations, including violations of the minimum wage. However, if the company ignores the guidance provided by the Labor Inspectorate and continues to commit violations, legal proceedings will be initiated and the case will be taken to court. The Head of the Manpower Sub-Department's revocation of the determination is inconsistent with applicable laws, namely Law Number 13 of 2003, Law Number 3 of 1951, and the Constitution of the Republic of Indonesia.